Qualified Legal Aid in Developed Democracies: A Comparative Legal Study - Podorozhna, Tetiana; Makarenko, Larysa; Andrusiv, Liudmyla; Kotukha, Oleksandr; Sanahurska, Halyna (International Journal of Criminology and Sociology, 2021)
Professional associations of lawyers play an important part in improving the quality of qualified legal aid. The largest association of legal professionals today is the International Bar Association. In September 1990, the International Bar Association adopted the Standards for the Independence of the Legal Profession, which are designed to enhance the role and importance of lawyers. Accordingly, as stated in the preamble to the Standards, they should be taken into account and respected by national governments when drafting national legislation and practice, as well as by all lawyers, judges, the representatives of executive and legislative power, and society at large. The purpose of the study is a comparative legal analysis of the features of providing qualified legal aid in developed democracies. The leading method during the study was comparative legal analysis. As a result of the analysis, it was concluded that the problem of guaranteeing the right to receive qualified legal aid is common to all modern states. But the ways to solve it differ, because the content of law as a statutory regulator of social relations is determined in the context of national systems and is deeply connected with their culture.